A SYSTEMATIC REVIEW OF THE EVALUATION OF NEONATAL SEPSIS DIAGNOSIS USING INTERLEUKINS - Adrianne, Samantha (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Aim: This study aims to summarize and evaluate the diagnostic potential and accuracy of interleukins (ILs) level as a diagnostic marker for neonatal sepsis.Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded.Results: Database searches identified a total of 19553 articles. Of these, 100 articles passed the screening process, resulting in 20 articles for full-text assessment. Among them, 11 articles did not evaluate the outcome of interest. Hence, we found 9 appropriate studies included. The ILs reported include IL-6, IL-10, IL-18, and IL-27, with the most common reported was IL-6.Conclusion: Current evidences supports the potential predictive utility of ILs level, especially IL-6, as a potential diagnostic marker for detecting neonatal sepsis. To determine the precise predictive efficacy of the marker, well-designed prospective studies had to be conducted due to the methodological variability and variation of the implemented thresholds.